Spirituality at Workplace and Job Satisfaction in an ASEAN context - Fanggidae, Roland Epafras (JOURNAL OF ECONOMIC SCIENCE, 2015)
Global competition between countries both economic and human resources will increase significantly. Agreements ASEAN countries to establish the ASEAN Free Trade Area (AFTA) the creation of global and regional competition. To deal with this phenomenon, the necessary transformation in the lives of the people, companies, and individuals. If you look at the success of Japan and China are becoming the new economic power, then the answer to this phenomenon is the